From rivals to neighbours: how time reduces aggression in two woodpecker species - Alena Fišerová; Matěj Máca; Max Linus Jankovic; Lucie Radová; Eliška Malcová; Petra Hurtová; Ondřej Fišer; Michaela Syrová; Roman Fuchs; Petr Veselý (Journal of Ornithology, 2026)

Leaky pollination barrier in edaphic vicarious alpine plants - Thomas Huber; Roman Fuchs; Julian Robin; Andreas Tribsch; Stefan Dötterl; Hanno Schaefer (Arthropod-Plant Interactions, 2025)
Adaptation to siliceous versus carbonate substrates is thought to be an important driver of speciation in the alpine flora. The role of the pollination system in the formation and maintenance of such species is presently unclear. Here, we chose three species pairs in the genera Gentiana , Primula , and Rhododendron which often occur in geographic proximity or even sympatry to study the existence of pollination barriers in these lineages. Using remote camera and direct observation approaches, scent and color analyses, we tested the hypothesis whether divergent pollinator communities exist that could help to maintain genetic separation of plant populations adapted to different soil types. We found differences in frequency, diurnal activity and to some extent also community composition of flower visitors in edaphic vicarious species pairs. Floral traits like color and scent as well as flower visitor co-distributions indicate that our study species have divergent but overlapping pollination systems. Our results do not suggest a strong reproductive barrier function of the pollination system. While adaptation to different soils still seems to be the main force keeping edaphic vicarious alpine plants genetically separated, pollinators might mediate hybridization in contact areas.

Size sometimes matters: recognition of known predators with artificially altered body size by untrained birds - Ondřej Fišer; Petr Veselý; Michaela Syrová; Michal Němec; Kateřina Kopecká; Eliška Perlová; Roman Fuchs (Animal Behaviour, 2024)

Species-specific breeding habitat association of declining farmland birds within urban environments: conservation implications - Jan Havlíček; Jan Riegert; Jaroslava Bandhauerová; Roman Fuchs; Martin Šálek (Urban Ecosystems, 2021)

Subtle Chemical Variations with Strong Ecological Significance: Stereoselective Responses of Male Orchid Bees to Stereoisomers of Carvone Epoxide - Katharina Brandt; Stefan Dötterl; Roman Fuchs; Daniela Maria do Amaral Ferraz Navarro; Isabel Cristina Sobreira Machado; Daniel Dobler; Oliver Reiser; Manfred Ayasse; Paulo Milet-Pinheiro (Journal of Chemical Ecology, 2019)

Large-scale commonness is the best predictor of bird species presence in European cities - Michal Ferenc; Ondřej Sedláček; Roman Fuchs; David Hořák; Lenka Storchová; Maurizio Fraissinet; David Storch (Urban Ecosystems, 2017)

Disentangling the influences of habitat availability, heterogeneity and spatial position on the species richness and rarity of urban bird communities in a central European city - Michal Ferenc; Ondřej Sedláček; Jindra Mourková; Alice Exnerová; Jaroslav Škopek; Jiří Formánek; Roman Fuchs (Urban Ecosystems, 2016)

Nest defense of the red-backed shrike Lanius collurio against five corvid species - Michal Němec; Roman Fuchs (acta ethologica, 2014)

How to improve urban greenspace for woodland birds: site and local-scale determinants of bird species richness - Michal Ferenc; Ondřej Sedláček; Roman Fuchs (Urban Ecosystems, 2014)

Importance of conspicuous colours in warning signals: the great tit’s (Parus major) point of view - Alena Cibulková; Petr Veselý; Roman Fuchs (Evolutionary Ecology, 2014)

Are cities different? Patterns of species richness and beta diversity of urban bird communities and regional species assemblages in E urope - Michal Ferenc; Ondřej Sedláček; Roman Fuchs; Marco Dinetti; Maurizio Fraissinet; David Storch (Global Ecology and Biogeography, 2014)
Aim To compare macroecological patterns between bird communities of E uropean cities and regional species assemblages in the surrounding landscape, and to reveal geographical trends in the urbanization of native avifauna. Location Forty‐one towns and cities in continental E urope. Methods We compiled data on the species richness and community composition of urban avifauna from 41 E uropean city breeding bird atlases, and of species assemblages comprising nine grid cells (each about 50 km × 50 km) from the EBCC A tlas of E uropean B reeding B irds (hereafter regional assemblages). Species–area relationships ( SAR s), latitudinal trends in diversity and the distance decay of community similarity were compared using regression models (generalized linear models). Observed urban communities were compared with randomly assembled ones to reveal systematic effects of the urban environment on native bird communities across E urope. We employed variance partitioning to quantify the relative effect of environmental parameters and the spatial position of cities on species richness. Results The species–area relationships did not differ significantly between cities and regional assemblages. Species richness of both types of communities increased towards higher latitudes, although the relationship was unimodal for regional assemblages, in contrast to cities. The increase in beta diversity with distance was on average less pronounced in cities than in regional assemblages, and was lower between individual cities than between communities of the same size randomly drawn from regional species assemblages. Moreover, average beta diversity was lower in northern cities, which are characterized by a relatively higher proportion of species from regional species pools. Main conclusions The species–area relationship and latitudinal trends are largely congruent between cities and the regional assemblages. However, city avifaunas tend to be relatively more uniform across space, revealing biotic homogenization. Urban communities in northern cities are more uniform as a higher proportion of bird species breeds in cities.

Tits recognize the potential dangers of predators and harmless birds in feeder experiments - Kateřina Tvardíková; Roman Fuchs (Journal of Ethology, 2012)

Do birds behave according to dynamic risk assessment theory? A feeder experiment - Kateřina Tvardíková; Roman Fuchs (Behavioral Ecology and Sociobiology, 2011)

Newly emerged Batesian mimicry protects only unfamiliar prey - Petr Veselý; Roman Fuchs (Evolutionary Ecology, 2009)

Territorial meadow pipit males (Anthus pratensis; Passeriformes) become more aggressive in female presence - Tereza Petrusková; Adam Petrusek; Václav Pavel; Roman Fuchs (The Science of Nature, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Habitat preferences of tree pipit (Anthus trivialis) and meadow pipit (A. pratensis) at sympatric and allopatric localities - Tereza Kumstátová; Tomáš Brinke; Soňa Tomková; Roman Fuchs; Adam Petrusek (Journal of Ornithology, 2004)